Development of design guideline incorporating cultural value consideration for green product / Ihwan Ghazali - Ihwan , Ghazali (2018)
Over the past few years, there have been a lot of efforts in promoting green products in developing countries. These efforts were driven by companies to not only focus on the profit orientation, but were encouraged with the involvement in protecting the environment through their products. However, issues may arise regarding the preferences of customers on the green products, which can be different to each other. These differences can be caused by many factors, including the influence of cultural values. These factors could complicate the designers in incorporating the green product features into their design that suit the customer preferences. Currently, there is a lack of guidelines for the consideration of cultural values into the green products design. Thus, the aim of this study was to construct a guideline to incorporate the influence of cultural values into the green products design. The sources of data were obtained from both the customers and designers perspectives. Indonesia and Malaysia were selected as the locations of study. For customers’ data, a questionnaire was distributed to collect the preferences from 1,256 samples (615 from Malaysia and the rest from Indonesia). Pre-testing was performed to ensure the reliability and validity of the questionnaire. The collected data was statistically analysed based on the satisfaction level, for the exploratory, confirmatory factor analysis and structural equation modeling. For designers’ data, the perspectives on the cultural consideration and design strategies to develop the green products were collected. The data collection was performed by conducting interviews for different profiles of designers. The results showed that the customer preferences in Malaysia were mostly influenced by the dimensions of uncertainty avoidance, long-term orientation and power distance. Under these influences, the Eco-label was identified as the most important strategy of green products, whereas the Indonesian customers were mostly influenced by the uncertainty avoidance and long-term orientation. In comparison to Malaysia, most of the Indonesian customers preferred to provide services for green products. A guideline was proposed to assist the designers in incorporating the cultural values influence into the green products design. The guideline was developed based on the identified cultural values, designers’ perspectives and literature analysis, to describe in more detail of the strategies for the green products design. The applicability of the guideline was validated using the case study. The designers agreed that the influence of cultural values is an important aspect that should be considered in the development of green products. Most of the designers also confirmed that the proposed guideline is useful to identify the customers’ needs and establish a design concept for the green products development. Based on the findings, this study confirmed that the consideration of cultural values can be used to evaluate the customer preferences on green products. Hence, a new guideline has been established, in order to assist designers in incorporating the cultural values into the process of designing the green products.